Verification and validation of a computational fluid dynamics (CFD) model for air entrainment at spillway aerators - Aydin, M. Cihan; Ozturk, Mualla (Canadian Science Publishing, Nrc Research Press, 2009)
The results of computational fluid dynamics (CFD) modeling obtained by using FLUENT software with respect to the air entrainment at spillway aerators are compared with data from a physical model study, as well as the results of some empirical equations and prototype observations presented by other investigators. The air-entrainment rates obtained from the CFD analyses are in reasonable agreement with the prototype data and the values calculated from empirical equations, and are better than the physical model data, which include considerable scale effects. The numerical verification procedure in this study is based on the American Society of Mechanical Engineers (ASME) editorial policy statement, which provides a framework for CFD uncertainty analysis. Thus, validation of the CFD is discussed within the scope of this study.
Keywords: scale effect; CFD; FLUENT; spillway aerators